2011
DOI: 10.1261/rna.2523911
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of hepatitis C viral RNA by cellular RNAi requires partitioning of Ago2 to lipid droplets and P-bodies

Abstract: The antiviral role of RNA interference (RNAi) in humans remains to be better understood. In RNAi, Ago2 proteins and microRNAs (miRNAs) or small interfering RNAs (siRNAs) form endonucleolytically active complexes which down-regulate expression of target mRNAs. P-bodies, cytoplasmic centers of mRNA decay, are involved in these pathways. Evidence exists that hepatitis C virus (HCV) utilizes host cellular RNAi machinery, including miRNA-122, Ago1-4, and Dicer proteins for replication and viral genome translation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
5
21
0
Order By: Relevance
“…Because Argonaute depletion did not alter P-body abundance (Fig. 5E), we hypothesize that the Argonaute proteins regulate HIV-1 infectivity by a mechanism which is independent of these foci, perhaps similar to Ago2-mediated regulation of hepatitis C virus replication (9).…”
Section: Discussionmentioning
confidence: 88%
“…Because Argonaute depletion did not alter P-body abundance (Fig. 5E), we hypothesize that the Argonaute proteins regulate HIV-1 infectivity by a mechanism which is independent of these foci, perhaps similar to Ago2-mediated regulation of hepatitis C virus replication (9).…”
Section: Discussionmentioning
confidence: 88%
“…This phenomenon was unlike that observed during poliovirus infection, where the abundance of Xrn1, Dcp1a, and Pan3 decreased by 5 h postinfection, likely as a result of virus-induced proteolytic cleavage (8). Rather, confocal microscopy showed that HCV likely dispersed P-bodies by relocalizing a number of P-body components (Lsm1, RCK/p54, DDX3, Dcp2, Xrn1, Ago2, and miR-122) to lipid droplets, the proposed sites of HCV assembly (7,9,10). Biochemical isolation and immunoblotting of lipid droplets con-firmed the localization of RCK/p54 and DDX3 on lipid droplets (9).…”
Section: Processing Bodies (P-bodies) and Hcvmentioning
confidence: 70%
“…Cross-linking and immunoprecipitation studies demonstrated that Ago2 interacted with HCV RNA not only at the known miR-122 binding sites but also in the IRES, E1, E2, NS5A, and NS5B regions (15). Ago2 and miR-122 colocalization at lipid droplets (10), and the additional Ago2-HCV RNA interactions (15), pose interesting questions concerning whether Ago2 might act beyond the microRNA-directed function during HCV infection. Furthermore, in light of the recent study describing adaptive mutations in HCV impacting miR-122-independent gene expression, would Ago2 still be required for HCV gene expression?…”
Section: P-body Components Affect Hcv Gene Expressionmentioning
confidence: 99%
“…Importantly, HCV does not hijack the whole RNAi machinery but only some components, in particular AGO2. This is supported by observations that HCV RNA-miR-122 complex reroutes some but not all components of the RNAi machinery to replication foci that are distinct from P bodies (79,80) . In fact, P-body disruption does not alter virus protein levels and virus production (80) .…”
Section: Ago2 and Hepatitis C Virusmentioning
confidence: 78%
“…In fact, P-body disruption does not alter virus protein levels and virus production (80) . Conversely, the HCV RNAs interact with P bodies when cleaved by artificially delivered siRNAs (79) . Together, these results unveil a new function for AGO2 in HCV replication, which (i) is mediated by the miR-122, (ii) probably occurs in a subcellular structures distinct from P bodies, and (iii) is beneficial for the virus.…”
Section: Ago2 and Hepatitis C Virusmentioning
confidence: 99%